2001
DOI: 10.1084/jem.193.9.1077
|View full text |Cite
|
Sign up to set email alerts
|

Invasion and Persistent Intracellular Colonization of Erythrocytes

Abstract: The expanding genus Bartonella includes zoonotic and human-specific pathogens that can cause a wide range of clinical manifestations. A productive infection allowing bacterial transmission by blood-sucking arthropods is marked by an intraerythrocytic bacteremia that occurs exclusively in specific human or animal reservoir hosts. Incidental human infection by animal-adapted bartonellae can cause disease without evidence for erythrocyte parasitism. A better understanding of the intraerythrocytic lifestyle of bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(80 citation statements)
references
References 37 publications
3
76
0
1
Order By: Relevance
“…However, although the endothelial vasculature undeniably plays a role in the early stages of infection, there is some experimental evidence that other putative cell types, such as erythrocytic precursors, may also serve as a niche for infecting bartonellae [29]. This hypothesis, however, conflicts with data obtained using the GFP- B. tribocorum- rat model that clearly indicated that encounter with, and invasion of, erythrocytes occurs in the bloodstream [3]. Furthermore, we have been unable to find any evidence for the presence of bartonellae in erythrocyte precursors isolated from the bone marrow of B. birtlesii -infected mice, despite rigorous efforts to do so (unpublished observations).…”
Section: Step 1: Infection Prior To Bacteraemiamentioning
confidence: 99%
“…However, although the endothelial vasculature undeniably plays a role in the early stages of infection, there is some experimental evidence that other putative cell types, such as erythrocytic precursors, may also serve as a niche for infecting bartonellae [29]. This hypothesis, however, conflicts with data obtained using the GFP- B. tribocorum- rat model that clearly indicated that encounter with, and invasion of, erythrocytes occurs in the bloodstream [3]. Furthermore, we have been unable to find any evidence for the presence of bartonellae in erythrocyte precursors isolated from the bone marrow of B. birtlesii -infected mice, despite rigorous efforts to do so (unpublished observations).…”
Section: Step 1: Infection Prior To Bacteraemiamentioning
confidence: 99%
“…Likewise, genes involved in hemin biosynthesis are present in Rickettsia but absent from Bartonella. Also, these differences correlate with lifestyle characteristics; Bartonella parasitizes erythrocytes (10)(11)(12) and is suggested to acquire essential iron molecules from the heme moiety of hemoglobin. Consistently, B. quintana and B. henselae have the highest reported hemin requirement for bacterial growth in vitro (39), and no genes for hemin biosynthesis were identified in either genome.…”
Section: Integration Of Megareplicon Sequences Members Of the Genusmentioning
confidence: 99%
“…In contrast, B. quintana contains only 18 repeat families, 12 of which are two-member families. The largest family in B. quintana contains seven tandemly repeated copies of the trwL gene located in one of the two operons coding for putative type IV secretion systems (12), and the second largest is a family of hemin-binding proteins (31).…”
Section: Fig 2 Schematic Illustration Of the Rearrangements Observementioning
confidence: 99%
See 1 more Smart Citation
“…Another Bartonella persistence strategy is invasion of and residence in the intracellular compartment of nonphagocytic host cells (9,10). Binding of Bartonella to different host-cell types likely involves adhesins that are variably expressed, but the Bartonella adhesins that are involved have not been identified definitively.…”
mentioning
confidence: 99%